Enhanced Living Environments Algorithms, Architectures, Platforms, and Systems - Ganchev, Ivan; Garcia, Nuno M.; Dobre, Ciprian; Mavromoustakis, Constandinos X.; Goleva, Rossitza (Information Systems and Applications, incl. Internet/Web, and HCI,, 2019)
This open access book is the final publication of the COST Action IC1303 "Algorithms, Architectures and Platforms for Enhanced Living Environments (AAPELE)" project. Ambient Assisted Living (AAL) is an area of research based on Information and Communication Technologies (ICT), medical research, and sociological research. AAL is based on the notion that technology and science can provide improvements in the quality of life for people in their homes, and that it can reduce the financial burden on the budgets of the healthcare providers. The concept of Enhanced Living Environments (ELE) refers to the AAL area that is more related with ICT. Effective ELE solutions require appropriate ICT algorithms, architectures, platforms, and systems, having in view the advance of science in this area and the development of new and innovative solutions. The aim of this book is to become a state-of-the-art reference, discussing progress made, as well as prompting future directions on theories, practices, standards, and strategies related to the ELE area. It was prepared as a Final Publication of the COST Action IC1303 "Algorithms, Architectures and Platforms for Enhanced Living Environments (AAPELE)". The book contains 12 chapters and can serve as a valuable reference for undergraduate students, post-graduate students, educators, faculty members, researchers, engineers, medical doctors, healthcare organizations, insurance companies, and research strategists working in this field.